Identification Of Heating Systems With An Application On An Electric Resistance Furnace - Chook, Kam Chee (2007)
Heating systems are commonly found in industries particularly in semiconductor fabrication and steel manufacturing. While there are several existing literatures on the modelling of different kinds of heating systems, very few have considered physical modelling validated by experimental data.